A Gender-based Approach to Parliamentary Discourse The Andalusian Parliament - Fuentes-Rodríguez, Catalina; Álvarez-Benito, Gloria (John Benjamins Publishing Company, 2016)
Does gender condition politicians' discourse strategies in parliament? This is the question we try to answer in A Gender-based Approach to Parliamentary Discourse: The Andalusian Parliament. This book, written by experts in the field of discourse analysis, covers key aspects of political discourse such as gender, identity and verbal and nonverbal strategies: intensification, enumerative series, non-literal quotations, pseudo-desemantisation, lexical colloquialisation, emotion, eye contact and time management. It provides a large number of examples from a balanced gender parliament, the Andalusian Parliament, and it focuses mainly on argumentation, since parliamentary discourse is above all argumentative. This book will prove invaluable to students and teachers in the field of discourse analysis, and more specifically of political discourse, and will also be very useful to politicians and anyone interested in communication strategies.